Comparison of Volleyball Skills of Rural and Urban Students in Bardiya - Bohara, Kishore; Bhatt, Gita; Chiluwal, Shailendra; Thapa, Suresh Bahadur (Far Western Review, 2024)
This study aims to compare the volleyball skills of rural and urban secondary school students in Bardiya district. A descriptive research method was employed, and respondents were selected using a random sampling technique. The AAHPER volleyball skill test, a standardized assessment tool, was utilized, comprising four specific skills: volleying, serving, passing, and setting. To analyze the data, various statistical techniques were applied as required. Each test item was compared separately between the rural and urban groups. The findings indicated that the mean scores of rural school students were higher for all four skills. A Z-test was conducted to determine the significance of the differences, revealing significant differences in each skill item. The study concluded that rural secondary school students in Bardiya district possess better volleyball skills compared to their urban counterparts. This conclusion is based on the higher mean scores and significant differences observed in the AAHPER volleyball skill test items. These findings suggest that rural students may have more opportunities or better conditions for developing their volleyball skills compared to urban students in this region. The findings of this study may be helpful to the coaches and selectors of players of volleyball game to find new players who possess potentiality to be good player of the game.